Free Nutritious Meals and Food Availability: Strengthening Community Nutrition for Indonesian Children - Sefita Tri Andini (Journal of Nutrition and Health Care, 2025)
Child malnutrition remains a major public health issue in Indonesia, particularly among children under five years old. In response, the government launched the Makan Bergizi Gratis (MBG) or Free Nutritious Meals program to provide balanced meals and reduce disparities in food access. However, its success depends on the integration of food availability, nutrition education, and community participation. This paper aims to describe the role of free nutritious meal programs and food availability in improving child nutrition and strengthening community food systems within the MBG framework. A descriptive qualitative approach was used through literature-based and policy analysis. Data and insights were synthesized from government reports, academic publications, and international references related to child nutrition, food systems, and public health programs from 2018–2025. The analysis highlights that the MBG program has the potential to improve children’s nutritional status when supported by local food production and consistent nutrition education. Community involvement is essential to ensure food diversity, safety, and sustainability. Strengthening partnerships among schools, health centers, and local producers can enhance program efficiency and long-term impact. The MBG initiative serves as more than a feeding program, it is a strategic approach to strengthen community nutrition. Integrating continuous education, local food empowerment, and community ownership can transform the program into a sustainable ecosystem for improving children’s health and achieving Indonesia’s vision of a healthy generation.